Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1515/hmbci-2021-0043
|View full text |Cite
|
Sign up to set email alerts
|

Synopsis of symptoms of COVID-19 during second wave of the pandemic in India

Abstract: COVID-19 was caused by the original coronavirus, severe acute respiratory syndrome associated coronavirus-2 (SARS CoV2), which originated in Wuhan, China. COVID-19 had a large breakout of cases in early 2020, resulting in an epidemic that turned into a pandemic. This quickly enveloped the global healthcare system. The principal testing method for COVID-19 detection, according to the WHO, is reverse transcription polymerase chain reaction (RT-PCR). Isolation of patients, quarantine, masking, social distancing, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 35 publications
1
9
0
1
Order By: Relevance
“…A similar result was reported in the change of mouth/mucosa color, with 13% reporting a change in mouth/mucosa color, dry mouth, loss of taste, bleeding gums, tooth pain, burning sensation in the mouth, mouth ulcers, severe tooth mobility/loosening, no symptoms, or any other oral traits were categorized. 8,9 Our study also found that dryness of the mouth was 36 (17.1%) in the second wave, compared to 4 (2.4%) in the first wave, pvalue 0.236. Similarly, with a significant p-value of 0.001, the loss of taste feature was 81(38.6 %) in the second wave and 52 (31.3%) in the first wave of COVID infection.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…A similar result was reported in the change of mouth/mucosa color, with 13% reporting a change in mouth/mucosa color, dry mouth, loss of taste, bleeding gums, tooth pain, burning sensation in the mouth, mouth ulcers, severe tooth mobility/loosening, no symptoms, or any other oral traits were categorized. 8,9 Our study also found that dryness of the mouth was 36 (17.1%) in the second wave, compared to 4 (2.4%) in the first wave, pvalue 0.236. Similarly, with a significant p-value of 0.001, the loss of taste feature was 81(38.6 %) in the second wave and 52 (31.3%) in the first wave of COVID infection.…”
Section: Discussionsupporting
confidence: 67%
“…14 In India, both the first and second waves of COVID infection led to an increase in oral manifestations. 8,9 In our study in eastern India, we also observed a variety of oral characteristics, such as dry mouth, bleeding gums, loss of taste, tooth discomfort, throat pain, tooth mobility, etc. It may not be the direct manifestation of COVID 19, but in the survey, patients reported increased dental visits after COVID-19 infection with symptoms, particularly in the second wave.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…COVID-19 transmission by infected, asymptomatic persons has been recorded since the outbreak's early offering significant COVID-19 containment issues. [9] During COVID-19 lockdown/confinement scenarios, exercise has been shown to prevent institutionalized older persons from functional decline. [10,11] Strength training improves both morphological (increasing the number of sarcomeres in parallel, increasing the synthesis of contractile assemblies of actin and myosin, and changing the composition of muscle fibers) and neural (improving neurological system and inter-muscular coordination) factors, as well as regulating the whole body metabolism.…”
Section: Exercise To Handle and Alleviate Physical Conditionsmentioning
confidence: 99%
“…In India, the second wave of COVID‐19 emerged in March 2021 (and started declining towards August 2021), with a new set of symptoms affecting the gastrointestinal system along with the previous (first wave) symptoms that primarily included respiratory problems (Kamble et al., 2021 ). Oxygen requirement, mortality rate and the disease‐spreading rate increased during the second wave even though vaccines like COVAXIN (inactivated whole virus vaccine) and COVISHIELD (adenovirus vectored vaccine) were available and in use since January 2021 (albeit in initial stages by the time second wave emerged in India).…”
Section: Introductionmentioning
confidence: 99%